2013
DOI: 10.1186/1743-422x-10-119
|View full text |Cite
|
Sign up to set email alerts
|

Consistent high concentration of the viral microRNA BART17 in plasma samples from nasopharyngeal carcinoma patients - evidence of non-exosomal transport

Abstract: BackgroundBecause latent Epstein Barr (EBV)-infection is a specific characteristic of malignant nasopharyngeal carcinoma (NPC), various molecules of viral origin are obvious candidate biomarkers in this disease. In a previous study, we could show in a few clinical samples that it was possible to detect a category of EBV microRNAs called miR-BARTs in the plasma of at least a fraction of NPC patients. The first aim of the present study was to investigate the status of circulating miR-BART17-5p (one of the miR-BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…In addition, Jones and Athanasiou [22] briefly reported the AUC for EBV-miR-BART7 (AUC = 0.81), which had an expression level independent from the circulating EBV DNA level. This result is consistent with that of Gourzones et al, [25] suggesting that circulating EBV-encoded miRNA can be used as serological markers in the absence of circulating EBV-DNA. Only Lu et al [27] compared specific miRNA levels between loco-regional and metastasis samples, and demonstrated a high sensitivity (73.7%) and specificity (74.2%) along with a high AUC value (0.743).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, Jones and Athanasiou [22] briefly reported the AUC for EBV-miR-BART7 (AUC = 0.81), which had an expression level independent from the circulating EBV DNA level. This result is consistent with that of Gourzones et al, [25] suggesting that circulating EBV-encoded miRNA can be used as serological markers in the absence of circulating EBV-DNA. Only Lu et al [27] compared specific miRNA levels between loco-regional and metastasis samples, and demonstrated a high sensitivity (73.7%) and specificity (74.2%) along with a high AUC value (0.743).…”
Section: Discussionsupporting
confidence: 94%
“…Basing on the inclusion and exclusion criteria, we included seven publications that contain nine studies on the diagnostic accuracy of circulating miRNA in NPC patients. [23][24][25][26][27][28][29][30] The flow of search strategy is shown in Figure 1. Table 1 lists the characteristics of the seven publications that compared circulating miRNA expression between NPC patients and healthy individuals.…”
Section: Literature Searchmentioning
confidence: 99%
“…Some EBV miRNAs are secreted and may be detected in plasma of nasopharyngeal carcinoma patients (38)(39)(40). Thus, EBV miRNA can be used as a biomarker predicting tumor progression and therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Comparisons of levels of EBV BART microRNA among NPC patients and non-NPC controls have been described in a few reports. [35][36][37] These studies suggested that EBV BART micro-RNA could be used as a biomarker for NPC. Circulating miRNAs have been reported as potentially promising markers for early detection, diagnosis, staging, progression, prognosis and response to treatment.…”
mentioning
confidence: 99%